Language assessment literacy and the professional development of pre-service foreign language teachers - Giraldo, Frank ([S.l.] : Universidad de Caldas, 2022)
Language teachers the world over inevitably need to engage in assessing their students' language ability for various purposes - diagnostic, progress, achievement, etc. Because language assessment is a major task for language teachers, language teaching programs should provide pre-service teachers with opportunities to problematize assessment in the foreign or second language classroom. Educating pre-service teachers for assessment should lead to positive consequences on their in-service work. In this book, the author provides a research-based approach to plan, design, implement, and evaluate a language assessment course for pre-service teachers. The following are some of the central issues addressed in the book: • A conceptualization of Language Assessment Literacy (LAL) -the central construct in the book- and its relationship with language teachers' professional development. • A theoretically and empirically driven approach for planning and designing a language assessment course. • A hands-on approach to teaching language assessment to pre-service language teachers. • Suggestions for teaching the design of assessments for the four language skills. • Suggestions for language teacher educators to discuss and derive ideas for assessment in their language teaching programs. • Real sample items and tasks for teaching and assessing pre-service teachers' LAL. The author constantly invites teacher educators to reflect upon the theory, research, and practice presented in the book. In doing so, he encourages these stakeholders to plan and teach language assessment courses that foster the LAL of pre-service teachers', an overlooked stakeholder group in LAL discussions."
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Language and languages -- Ability testing; Language teachers -- Training of; Langage et langues -- Tests d'aptitude.; Language Experience Approach; EDUCATION; Teaching Methods & Materials; Language and languages -- Ability testing; Language teachers -- Training of